Mit a golfuith staar een hæst. La descrizione di Babilonia negli adattamenti scandinavi di Floire et Blancheflor - Dell’Aquila, Erika (Annali di Ca’ Foscari: Serie Occidentale)
This article examines the relationship between three versions of Floire et Blancheflor: the Old French Conte de Floire et Blancheflor, the Old Norse Flóres saga ok Blankiflúr, and the Old Swedish Flores och Blanzeflor. By comparing a specific episode – the description of the city of Babylon – the study identifies similarities and differences to clarify the debated origin of the Swedish text. The focus is on providing an updated overview of Floire et Blancheflor’s transmission in Scandinavia and deepening the understanding of Flores och Blanzeflor’s transmission. The analysis highlights how specific details and variations reflect the processes of translation and adaptation across different cultural contexts.